REBELLION AGAINST THE CONSERVATIVE IN MIKE NEWELL'SMONALISA SMILE A FEMINIST APPROACHResearch PaperSubmitted as a partial fulfillment of the requirementsfor Getting Bachelor degree of Educationin English DepartmentBy:KARLINA HENDRA DEWI - DEWI, KARLINA HENDRA (2007)
This research paper elaborated the portraits of women traditional role in Mike Newell's Mona Lisa Smile, that are analyze the structural elements of the film and to analyze, the structural elements of the film based on feminist perspective by identifying the film relationship between the film and the social background of American society in the late of twentieth and early twenty first centuries. The researches belong to a qualitative research. The data of he research is the dialogue and the film entailed Mona Lisa Smile, whereas the at source from both primary data source such as biography of the director, website and other sources about the film, the approach and the social background of American society that support the analysis. The method to analyze the data is descriptive analysis. After analyzed the film, the researcher come to the conclusion: the portraits of women traditional role Mona Lisa Smile are mostly found in the characters drawn by Mike Newell, who always kept and hold the conservative values of Wellesley College, the theme describe that woman could do anything that they want, and be anything that they want to be without considering women stereotype made by society, and because women have the same natural rights like men.